“Tigres de papel”? As bancadas BBB entre a imagem pública e a atuação efetiva na Câmara dos Deputados Federais, 2011-2014 - Carvalho, Juliana Aparecida Sousa [UNIFESP] (2020)
This dissertation aims to discuss the legislative performance of what became known as “bancadas BBB” - a group made up of the evangelical bench and the Parliamentary Fronts of Agriculture and Public Security - during the 54th Legislature of the Chamber of Deputies (2011-2014). Our objective is to verify if there is empirical evidence that this group is changing the organization patterns of the Brazilian legislative, based mainly on the production and approval of laws proposed by members of the “bancadas”. The principal hypothesis is that as long as the operating rules governing the activities of federal deputies - which make work centered on parties and the Executive - remain unchanged, nor will the patterns of behavior change. To test it, we based this research on the propositions, approvals and nominal votes that took place in the period analyzed, as well as on the profile of these parliamentarians. The results allow us to point out that even though the presence of these suprapartisan groups is growing in Congress, their strength as a collective actor cannot yet be proved in terms of legislative production.